Systematics of the Baikalian Babr (Crustacea: Amphipoda: Pallaseidae) - Daneliya, Mikhail E.; Kamaltynov, Ravil M.; Kontula, Tytti; Väinölä, Risto (Zootaxa, 2009)
From morphogical and molecular data we reconsider the systematic composition of the Lake Baikal amphipod genusBabr Kamaltynov & Väinölä (Pallaseidae), until recently part of Pallasea Bate. The morphology of Babr is relativelyuniform, but both allozyme and mitochondrial DNA data recognize a deep split into two lineages (Nei's D = 1.1,uncorrected COI sequence divergence 17 %). These correspond with the two species B. baikali (Stebbing) andB. nigromaculatus (Dorogostaisky), which both are found to be widespread throughout the lake but show different depthpreferences. We found no support for the third proposed taxon B. inermis (Sowinsky), and consider it a synonym ofB. baikali. Revised morphological diagnoses for the genus and the two species are presented, including newmorphological characters. In terms of mtDNA, B. baikali is further subdivided into clearly separate geographical lineages, for which no morphological correspondence was however established.